In silico, in vitro and in vivo analysis of putative virulence factors identified in large clostridial toxin-negative, binary toxin- producing C. difficile strains. (December 2019) - Androga, G.O.; Knight, D.R.; Hutton, M.L.; Mileto, S.J.; James, M.L.; Evans, C.; Lyras, D.; Chang, B.J.; Foster, N.F.; Riley, T.V.
Abstract: The relevance of large clostridial toxin-negative, binary toxin-producing (A − B - CDT + ) Clostridium difficile strains in human infection is still controversial. In this study, we investigated putative virulence traits that may contribute to the role of A − B - CDT + C. difficile strains in idiopathic diarrhea. Phenotypic assays were conducted on 148 strains of C. difficile comprising 10 different A − B - CDT + C. difficile ribotypes (RTs): 033, 238, 239, 288, 585, 586, QX143, QX444, QX521 and QX629. A subset of these isolates ( n = 53) was whole-genome sequenced to identify genetic loci associated with virulence and survival. Motility studies showed that with the exception of RT 239 all RTs tested were non-motile. C. difficile RTs 033 and 288 had deletions in the F2 and F3 regions of their flagella operon while the F2 region was absent from strains of RTs 238, 585, 586, QX143, QX444, QX521 and QX629. The flagellin and flagella cap genes, fliC and fliD, respectively, involved in adherence and host colonization, were conserved in all strains, including reference strains. All A − B - CDT + C. difficile strains produced at least three extracellular enzymes (deoxyribonuclease, esterase and mucinase) indicating that these are important extracellular proteins. The toxicity of A − B - CDT + C. difficile strains in Vero cells was confirmed, however, pathogenicity was not demonstrated in a mouse model of disease. Despite successful colonization by most strains, there was no evidence of disease in mice. This study provides the first in-depth analysis of A − B - CDT + C. difficile strains and contributes to the current limited knowledge of these strains as a cause of C. difficile infection. Highlights: A − B - CDT + C. difficile RTs have survival, transmission and putative virulence factors. With the exception of RT 239 all A − B - CDT + C. difficile RTs tested were non-motile. All A − B - CDT + C. difficile strains produced at least three extracellular enzymes. Cytotoxicity of A − B - CDT + C. difficile strains was demonstrated in vitro. Pathogenicity was not seen in a mouse model despite successful colonisation.